Laparoscopic Sentinel Lymph Node Detection After Hysteroscopic Injection of Technetium-99 in Patients With Endometrial Cancer. Issue 3 (March 2015) - Favero, Giovanni; Pfiffer, Tatiana; Ribeiro, Altamiro; Carvalho, Jesus Paula; Baracat, Edmund Chada; Mechsner, Sylvia; Chiantera, Vito; Köhler, Christhardt; Schneider, Achim
<x xml:space="preserve">Abstract</x> Background and Objectives Endometrial cancer (EC) has an increasing incidence worldwide. Despite the unequivocal prognostic importance of nodal status, systematic lymphadenectomy is associated to elevated morbidity. Sentinel lymph node (SLN) biopsy is designed to avoid extensive nodal dissection and provide crucial oncologic information. The goal of this prospective study was to determine the feasibility, safety, and accuracy of laparoscopic SLN biopsy in EC obtained through hysteroscopic injection of technetium-99 (Tc-99). Methods From January 2008 to December 2012, a total of 42 women with EC were included in the study. We injected 20 mBq of Tc-99 hysteroscopically underneath the tumor minutes before definitive surgery. Thereafter, laparoscopic SLN identification /biopsy followed by pelvic and para-aortic lymphadenectomy, hysterectomy, and bilateral salpingo-oophorectomy were executed. Results The total number of removed nodes was 970. The detection rate of the method was 73% (31/42). Among the 70 isolated SLNs, 35% (24) were exclusively identified in the para-aortic area. Fourteen patients (45%) had SLN only in the pelvic region, whereas 11 (35%) had SLN in both pelvic and para-aortic areas and 6 women (20%) had isolated para-aortic SNL. Nodal metastases were histologically confirmed in 9 patients (22%), and SLN was identified in 7 of 9 patients (78%). Although the obtained specificity was 100% and the negative predictive value was 89%, the sensitivity was only 58% (false-negative rate of 42%). Conclusions We could demonstrate that endoscopic SLN biopsy obtained through hysteroscopic injection of Tc-99 is a feasible and safe method. Despite the restricted number of included patients in this series, the obtained sensitivity and false-negative rates raise some questions about the real accuracy of the procedure in EC. Larger validation trials requiring quality pelvic and para-aortic lymphadenectomy are essential to correctly evaluate the method.